MYC Levels Regulate Metastatic Heterogeneity in Pancreatic Adenocarcinoma - Maddipati, Ravikanth; Norgard, Robert J.; Baslan, Timour; Rathi, Komal S.; Zhang, Amy; Saeid, Asal; Higashihara, Taku; Wu, Feng; Kumar, Angad; Annamalai, Valli; Bhattacharya, Saurav; Raman, Pichai; et al. (Cancer discovery, 2022)
The degree of metastatic disease varies widely among patients with cancer and affects clinical outcomes. However, the biological and functional differences that drive the extent of metastasis are poorly understood. We analyzed primary tumors and paired metastases using a multifluorescent lineage-labeled mouse model of pancreatic ductal adenocarcinoma (PDAC)-a tumor type in which most patients present with metastases. Genomic and transcriptomic analysis revealed an association between metastatic burden and gene amplification or transcriptional upregulation of and its downstream targets. Functional experiments showed that MYC promotes metastasis by recruiting tumor-associated macrophages, leading to greater bloodstream intravasation. Consistent with these findings, metastatic progression in human PDAC was associated with activation of MYC signaling pathways and enrichment for amplifications specifically in metastatic patients. Collectively, these results implicate MYC activity as a major determinant of metastatic burden in advanced PDAC. SIGNIFICANCE: Here, we investigate metastatic variation seen clinically in patients with PDAC and murine PDAC tumors and identify MYC as a major driver of this heterogeneity. .